10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Work-integrated learning (WIL), a cornerstone of the university education of health information managers, combines academic theory with workplace-based practice to enhance graduate career-readiness. Recent curriculum changes to the two health information management (HIM) degrees at La Trobe University, Australia, involved the adoption of a project-based learning (PjBL) model, replacing an internship model, for final-year (capstone) professional practice placements. The University's project placement documentation was comprehensively revised to inform and support healthcare industry supervisors in accommodating these changes. OBJECTIVE: To investigate industry supervisors' perceptions of the effectiveness of documentation re-developed to frame and support project-based, final-year professional practice (WIL) placements. METHOD: A cross-sectional study design utilised a self-administered, online survey of the industry supervisors of the 2024 final-year HIM placement students. The survey instrument captured feedback on the usability and user-friendliness of the first iteration of revised project documentation, including supervisor guidelines. RESULTS: Most respondents (93%) reported that the guidelines clarified project-based placement requirements, with 80% rating them as useful or very useful. The revised proposal template was perceived to be user-friendly by 93% of industry supervisors. Suggested areas for improvement included clearer articulation of student skillsets, provision of examples of previous placement projects, and enhanced guidance and support for creating and writing learning outcomes (LOs) to frame project-based placements. CONCLUSION: Evidence-informed documentation supports authentic, inquiry-driven professional practice placements that successfully bridge theory and practice. The study produced recommendations for strengthening PjBL placement documentation to assist industry supervisors of final-year students, including refinements to (a) enhance usability of the new iteration of the placement documentation, (b) inform the development of robust LOs aligned with the national HIM professional competency standards, and (c) emphasise projects pitched to match student capabilities.Implications for health information management practice:This study has advanced our knowledge of WIL in HIM education by demonstrating how purposeful, stakeholder- and education theory-informed documentation can guide industry supervisors in applying a project-based approach. Embedding the PjBL model and principles into HIM placements provides opportunities for augmenting the development of profession-ready graduates, and for underpinning students' acquisition of the transferable skills essential for navigating complex HIM environments.